Market research and its use in decision making (GEON Journal (Management, Organizations and Business), 2016)
Companies today must face the changes brought by globalization, which has been a difficult task for some employers who insist on developing strategies empirically generated in some cases making bad decisions that eventually are reflected in corporate vulnerability to the changing market; Following this problematic market research can be considered as a solution to this phenomenon, since as a systematic process provides the amount of information needed and states that seeks to support decision-making, after meeting the internal and external factors affecting the company, and situations of great importance for achieving competitiveness and sustainability in the market that every day becomes more demanding about the buying behavior of consumers, distribution channels, product characteristics and other aspects which influence the corporate image and performance of organizations. In addition to this, it offers benefits that enable more efficient design strategies that finally marketing, will bring a series of positive responses summarized in an organizational growth.
Keywords: Market research; globalization; information; competitiveness; consumer